Tingkat Erodibilitas Tanah pada Budidaya Tanaman Tomat (Lycopersicon esculentum Mill.) dengan Berbagai Jenis Mulsa Plastik dan Jerami - I Muna Bhaskara; I Wayan Tika; I Made Anom S. Wijaya (Program Studi Teknik Pertanian, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2020)
Erodibility of the soil is the sensitivity of the soil to erosion, the higher erodibility value of the soil the easier the soil erodes. One way to reduce the rate of erosion is by covering the soil with mulch. The purpose of this study is (1) to know the effect of plastic mulch and straw on the cultivation of tomato plants on the level of soil erodibility and (2) to know the type of mulch which gives the lowest soil erodibility level in tomato cultivation. The design in this study uses a Completely Randomized Design with treatment consisting of tomato plants planted without mulch, tomato plants planted using black plastic mulch, tomato plants planted using silver plastic mulch, tomato plants planted using transparent and tomato plants planted using straw. The results showed that the treatment without mulch and treatment with straw had increased erodibility values, while the treatment using black plastic and using silver plastic had decreased erodibility value. In the treatment with transparent mulch there is no effect in erodibility value. Each treatment had different values but had the same level of category, which is very high. The type of mulch who had the lowest value is the treatment silver plastic mulch with an erodibilitas value of 0,58 at the beginning of cultivation and 0,55 at three months of planting age. Keywords: Soil erodibility, tomato plants, mulch.